Peran Orang Tua dalam Pendidikan Karakter Peserta Didik Selama Masa Pandemi COVID-19: Sebuah Kajian Pustaka - Yunanda Cucu Pratama Agustin (Yayasan Citra Dharma Cindekia, 2024)
The COVID-19 pandemic has brought significant changes to the education system, particularly through the implementation of distance learning. This situation has increased parents' responsibilities in supporting not only children's academic achievement but also their character development at home. This study aims to examine the role of parents in strengthening students' character education during the COVID-19 pandemic through a literature review approach. The study employed a qualitative descriptive method using literature review by analyzing relevant scientific journal articles published between 2020 and 2024. The literature was collected through academic databases and analyzed using content analysis to identify common findings regarding parents' involvement in character education. The results indicate that parents play a fundamental role as educators, role models, supervisors, motivators, and facilitators during home-based learning. Effective collaboration between parents and schools contributes positively to the development of students' responsibility, discipline, honesty, independence, and religious values. However, several challenges were identified, including parents' limited time, differences in educational background, work responsibilities, and inadequate understanding of character-based learning. Therefore, strengthening communication between schools and families, along with providing guidance for parents, is essential to optimize character education. This review highlights that parents' active involvement is a key factor in maintaining the continuity of character education during educational disruptions such as the COVID-19 pandemic.